DENSITY AND COVERAGE OF SEAGRASS ON DIFFERENT TYPE OF SEDIMENT AT PANDARATAN BEACH TAPANULI TENGAH REGENCY NORTH SUMATERA PROVINCE - Lianov, Dea; Efriyeldi, Efriyeldi; Zulkifli, Zulkifli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Seagrass ecosystem is one of shallow sea ecosystems that plays an important role to maintain stability of the sea. Density and coverage of seagrass depend on characteristic of sediment, include mean size and the type of sediment. The purpose of this study was to find out how density and coverage of seagrass on different type of sediment at Pandaratan Beach Tapanuli Tengah Regency North Sumatera Province. This research was conducted in April 2019. From the results can be discovered that there are two species of seagrass that found in Pandaratan Beach, Cymodocea rotundata and Enhalus acoroides. In the type of muddy sand sediment has the heighest density of seagrass which is 309 ind/m2 and categorized into very tight. In the type of sandy gravel sediment has the lowest density of seagrass which is 49 ind/m2 and categorized into very rare. And in the type of gravely sand sediment has the density of seagrass that is 234 ind/m2 and categorized into very tight. In the type of muddy sand sediment has the heighest coverage of seagrass which is 50.18% and categorized into good. In the type of sandy gravel sediment has the lowest coverage which is 17.72%. And in the type of gravely sand sediment has the coverage of seagrass which is 26.95% and categorize into moderately